Benzo[g]quinazolin-based scaffold derivatives as dual EGFR/HER2 inhibitors - Mostafa M. Ghorab; Mansour S. Alsaid; Aiten M. Soliman; Abdullah A. Al-Mishari (Taylor & Francis Group, 2018)
Targeting EGFR has proven to be beneficial in the treatment of several types of solid tumours. So, a series of novel 2-(4-oxo-3-(4-sulfamoylphenyl)-3,4-dihydrobenzo[g]quinazolin-2-ylthio)-N-substituted acetamide 5-19 were synthesised from the starting material 4-(2-mercapto-4-oxobenzo[g]quinazolin-3(4H)-yl) benzenesulfonamide 4, to be evaluated as dual EGFR/HER2 inhibitors. The target compounds 5-19, were screened for their cytotoxic activity against A549 lung cancer cell line. The percentage inhibition of EGFR enzyme was measured and compared with erlotinib as the reference drug. Compounds 6, 8, 10, and 16 showed excellent EGFR inhibitory activity and were further selected for screening as dual EGFR/HER2 inhibitors. The four selected compounds showed IC50 ranging from 0.009 to 0.026 µM for EGFR and 0.021 to 0.069 µM for the HER2 enzyme. Compound 8 was found to be the most potent in this study with IC50 0.009 and 0.021 µM for EGFR and HER2, respectively.